Influence of irradiation on the phase equilibrium parameters in liquids - L. A. Bulavin; D. A. Gavryshenko; K. V. Taradiy; N. A. Atamas; V. M. Sysoev (Ядерна фізика та енергетика)
The work is dedicated to the investigation of irradiation influence on those properties of liquid systems, which are defined by the change of chemical potential of the liquid and its components under the influence of irradiation. It was shown that irradiation of the coexistent phases at the stationary state leads to the shift of phase transition point parameters. The shift of the temperature and pressure of the phase transition was obtained for the first order phase transitions under the influence of irradiation. Both entropy and energetic factors were included in chemical potential of the regarded system. The main regularities of irradiation influence on the solubility of solid in liquids were obtained.